Decolonizing colonial development models in Africa a new postcolonial critique - Allen, Fidelis; Amadi, Luke, 1978- (Lexington Books, 2022)
"This book confronts colonial development models to decolonize the methodologies and epistemologies of development in Africa and advocate for Afrocentric alternatives. Using postcolonial, post-developmental, and post-structural theories, the authors advocate for a new direction of development that incorporates indigenous-Afrocentric alternatives"--